The tear substitutive therapy for prophylaxis and treatment of dry eye after cataract surgery - V. N. Trubilin; T. A. Sedneva; S. G. Kapkova (Oftalʹmologiâ)
Purpose: To study the efficiency of tear substitutes based on hyaluronic acid at the patients after phacoemulsification for prophylaxis and postoperative therapy of dry eye syndrome.Methods: 168 patients (168 eyes) were examined before cataract surgery. The average age was 69.2±5.7 years old. Patients were divided into four groups according to the presence of eye dry syndrome and following tear substitutive therapy. 55 patients with a mild case of DES (the first group) were treated with Vismed® eye drops 1 drop given 3 times a day for 1 week before surgery and postoperatively. 10 patients with a moderate case of DES (second group) were treated with Vismed gel® to use with the same periodicity. Patients without DES were divided into two groups: 50 of them (third group) were treated to use Vismed® 1 drop 3 times a day postoperatively, the rest 53 didn’t undergo the course of treatment — «checkout group». The observation period was 45 days after operation. The study of tear secretion and osmolarity of tear fluid was performed before and after operative period.Results: 65 patients were first diagnosed a mild or moderate case of DES. On the third day after operation every group showed the increase of tear osmolarity, it was especially noticable among the patients of «checkout group» from 294 to 314 mOsm / l at the average. On the seventh day after operation all groups showed further negative dynamics, and in the «checkout» group comparing to initial indices was registered noticable worsening of the studied parameters (р≤0.05). By the 14th day after phacoemulsification patients from the 1st and the 3rd groups displayed the tendency to restoration of indices to the preoperative values. Indices of osmolarity and tear secretion restored among the patients from the 1st and the 2nd groups by the 21st day and even improved in comparison to the preoperative values of group 3. Meanwhile, «checkout» group’s indices fell to a level even lower than before the operation. By the end of the experiment (45th day after operation) decrease of osmolarity and increase of functional tests was registered among all the groups, however, the results were more evident among the groups who underwent tear substitutive treatment.Conclusion: Performed experiment confirmed that tear substitutive therapy conducted in the postoperatively speeds up recovery and restores indices of tear secretion and osmolarity.